2008
DOI: 10.1159/000161054
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism and Brain Morphology in Mild Cognitive Impairment

Abstract: Background: The apolipoprotein E (ApoE) genotype has been confirmed as the major genetic risk factor for late-onset Alzheimer’s disease (AD). How the ApoE genotype and brain morphology relate to each other is only partly understood, particularly in mild cognitive impairment, the assumed prestage of AD. Methods: A total of 83 subjects with mild cognitive impairment (aging-associated cognitive decline criteria) were investigated with optimized voxel-based morphometry (VBM). We tested for differences in gray and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…However, except for the influence of gender, age, and level of education, current study found a consistent association between the ε 4 allele and MCI in both the Han and the Hui ethnic groups, and these findings were similar to that of other studies [31]. MCI was the most commonly accepted prodromal AD stage; this suggests that the apoE ε 4 allele has relevance for MCI screening [32, 33]. …”
Section: Discussionsupporting
confidence: 89%
“…However, except for the influence of gender, age, and level of education, current study found a consistent association between the ε 4 allele and MCI in both the Han and the Hui ethnic groups, and these findings were similar to that of other studies [31]. MCI was the most commonly accepted prodromal AD stage; this suggests that the apoE ε 4 allele has relevance for MCI screening [32, 33]. …”
Section: Discussionsupporting
confidence: 89%
“…The extent of the cortical and hippocampal volume loss is similar to previous studies of mild-moderate AD [11,12,[49][50][51] . Previous volumetric studies assessing the influence of APOE genotype on hippocampal volume in AD have reported conflicting evidence: whilst several have reported lower hippocampal volume with increasing 4 dose [7,52,53] , others have failed to find such a relationship [44,54,55] .…”
Section: Discussionsupporting
confidence: 87%
“…[34][35][36][37][38][39][40][41] The present study recruited individuals without subjective or objective cognitive impairment, hence subjects with normal cognition, to test the effects of APOE4 on the brain functioning of WM by using BOLD fMRI. Performance of n-back WM was not different between groups (P ϭ .41-.85), similar to the findings of a previous publication.…”
Section: Discussionmentioning
confidence: 99%